A decision analysis guideline for underground bulk air heat exchanger design specifications - M. Hooman; R. C. W. Webber-Youngman; W. M. Marx (The Southern African Institute of Mining and Metallurgy, 2015)
This paper discusses a study that investigated different underground bulk air heat exchanger (>100 m3/s) design criteria. A literature review found that no single document exists covering all design criteria for different heat exchangers, and therefore the need was identified to generate a guideline with decision analyser steps to arrive at a technical specification. The study investigated the factors influencing heat exchanger designs (spray chambers, towers, and indirect-contact heat exchangers) and the technical requirements for each. The decision analysers can be used to generate optimized, user-friendly fit-for-purpose designs for bulk air heat exchangers (air cooler and heat rejection). The study was tested against a constructed air cooler and heat rejection unit at a copper mine1. It was concluded that the decision analysers were used successfully. This tool (decision analysers) can be used by engineers for the efficient and cost-effectively design of heat exchangers.